Research on Problems and Countermeasures of Financial Management (Asian Business Research, 2022)
In the course of my country's economic development, the financial school is not allowed to be ignored. Due tothe vigorous development of my country's economic market in recent years, financial institutions, all majorfinancial institutions, asset management enterprises, and securities companies, etc., are urgently demand forfinancial majors, and these demands also give financial learning. More challenges from development. Today'sdevelopment is closely related to people's lives and production, but the financial industry has changed a certainchange as the economic market changes.